P607 Higher adalimumab serum levels do not increase the risk of adverse events in patients with inflammatory bowel disease. (25th January 2019) - Narula, N; Lauzon, B; Marshall, J
Abstract: Background: The relationship between serum adalimumab concentrations and adverse events in patients with inflammatory bowel disease (IBD) is unknown. We aimed to determine whether patients with IBD using adalimumab are at increased risk of adverse events if they have high adalimumab serum levels compared with those with lower adalimumab levels. Methods: This was a retrospective study of 133 IBD patients with at least one measurement of serum adalimumab level available. The cohort was divided according to the median adalimumab level of 9.8 μg/ml. The primary outcome was the rate of overall adverse events between the two groups. Secondary outcomes included the rate of infections, dermatologic reactions, injection-site reactions, and other adverse events in both groups. Rates of discontinuation of adalimumab due to adverse events was also evaluated. Multi-variate logistic regression analysis was also performed to evaluate the relationship between adalimumab levels and adverse events. Results: A total of 27 adverse events were reported in 133 patients in the overall cohort. In patients with higher adalimumab levels, there were 17 adverse events reported in a total of 66 patients, which was not significantly different than the 10 adverse events reported in 67 patients with lower adalimumab levels (25.7% vs. 14.9%, p = 0.12). Stratification of patients into adalimumab level tertiles did not show any difference in the rate of adverse events between the three groups. After adjustment for potential covariates, IBD patients with higher adalimumab levels did not have higher odds of an adverse event than patients with lower levels (OR 1.94, 95% CI 0.81–4.64). Conclusions: There does not appear to be an increased risk of adverse events in IBD patients with higher adalimumab levels.